EVALUATION OF PRO-APOPTOTIC EFFECTS OF β-MONOLINOLEIN ON METASTATIC BREAST CANCER CELL LINE MDA-MB-231 - SOFI, MOHAMMED SHAFI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of this study was to evaluate the β-monolinolein as a potential therapy for breast cancer treatment. Methods: The cytotoxic activity of β-monolinolein was evaluated by 3-(4,5-dimetylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and trypan blue exclusion assay. The cellular cytotoxicity and levels of cytosolic enzyme, lactate dehydrogenase (LDH), were measured by assessing μmoles of nicotinamide adenine dinucleotide/well/min. To confirm whether β-monolinolein induces apoptosis in 3,4-methylenedioxyamphetamine (MDA)- MB-231 cells, western blot and semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) analysis were performed. Results: For the 1st time, it was demonstrated that β-monolinolein strongly inhibits the growth of MDA-MB-231 cells, with an half maximal inhibitory concentration value of 12.5 μg/ml. <90% of cell death was achieved at higher concentrations after 48 h of treatment. Trypan blue assay showed that the cell viability was significantly decreased in a dose-dependent manner in MDA-MB-231 cells after 48 h of treatment. On the other hand, LDH activities in the cultured media were significantly elevated in a dose-dependent manner as compared to the control. Further, the western blot analysis showed that β-monolinolein leads to change in expression levels of important cell cycle regulators such as p21, Bax, Bcl-Xl, and Bcl-2 in MDA-MB-231 cells. The semiquantitative RT-PCR results indicated a significant upregulation of proapoptotic genes such as p53, p21, and Bax and downregulation of antiapoptotic gene Bcl-2. Conclusion: These results indicate that β-monolinolein leads to change in expression of various cell cycle/apoptotic regulators and hence induces death in MDA-MB-231 cells.